Energy transition - Cassoret, Bertrand (Boca Raton : CRC Press, 2021)
This book presents both the importance of energy transition and its associated difficulties. Energy Transition, Second Edition, provides an explanation of the physical concepts of energy and power and also reviews global energy consumption and our dependence on energy. The book discusses the links between the economy and energy. It explains the drawbacks and dangers of different energy sources and tries to compare them. By reviewing future energy resources, it evaluates several transition scenarios. The book shows that the laws of physics prevent the emergence of simple, pleasant solutions, but it proposes potential solutions and encourages readers to develop better processes from energy sources to production to consumption. This book will be of interest to engineers and undergraduate and graduate students studying and working in various fields of energy; producers of fossil, gas, oil, coal, electric, renewable, and nuclear energy; and anyone interested in better understanding these fundamental problems for our future. FEATURES Discusses the current issues with energy transition Covers several energy transition scenarios and their associated difficulties Presents the links between economy and energy Highlights the importance of a global discussion of energy Encourages the development of better, improved processes in energy sources from production to consumption
1. What Is Energy?2. Energy Consumption in France and across the World3. The Importance of Energy4. Pollution, Risks and Problems Related to Energy Sources5. A Comparison of Energy Sources: Related Dangers and Issues6. Energy Resources7. Energy Transition Scenarios8. Energy Efficiency and Sobriety9. Money, Too Expensive10. Energy Myths and Legends11. So, What Should We Do?12. Conclusion, Prospects
OCLC-licensed vendor bibliographic record.
Keywords: Renewable energy sources; Power resources; Sustainable urban development; Energy policy; NATURE / Environmental Conservation & Protection; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development; SCIENCE / Energy